Expressão de microRNA derivados de leucócitos associada à disfunção sistólica do ventrículo esquerdo em indivíduos que sofreram infarto agudo do miocárdio - Komatsu, Raquel Costa Silva Dantas (2023)
Left ventricular systolic dysfunction (LVEDD) is considered a serious consequence of ST-segment elevation myocardial infarction (STEMI) and finding biomarkers of LVEDD is necessary. Thus, immune cell-derived microRNAs stand out as they mediate complications associated with AMI. Therefore, this study aims to evaluate the association of leukocyte-derived microRNA with the development of post-STEMI LVSd. Post-STEMI patients were grouped as having (LVSd, n=9) or not LVSd (nonLVSd, n=16). The expression of 61 microRNAs was analyzed by RT-qPCR and the differentially expressed microRNAs were identified. Principal Component Analysis evaluated the stratification of groups based on microRNA expression. Predictive variables of LVSd were investigated through logistic regression analysis. A system biology approach was used to explore the regulatory molecular network of the disease and an enrichment analysis was performed. The let-7b-5p (AUC: 0.807; 95% CI: 0.63– 0.98; p = 0.013), miR-125a-3p (AUC: 0.800; 95% CI: 0.61–0.99; p = 0.036) and miR326 (AUC: 0.783; 95% CI: 0.54–1.00; p = 0.028) were upregulated in LVSd (p < 0.05) and discriminated LVSd from non-LVSd. Multivariate logistic regression analysis showed let-7b-5p (OR: 16.00; 95% CI: 1.54-166.05; p = 0.020) and miR-326 (OR: 28.00; 95% CI: 2.42-323.70; p = 0.008) as predictors of LVSd. The enrichment analysis of the targets of these three microRNAs is associated with immunological response, cell-cell adhesion, and cardiac changes. Therefore, the expression of let-7b-5p, miR326, and miR-125a-3p was associated with post-STEMI LVSd, indicating their potential involvement in the cardiac dysfunction physiopathology and highlighting these microRNAs as possible LVSd biomarkers.